Effectiveness of the Project-Based Learning Model on High School Students' Argumentative Essay Writing Skills - Ainu Zuhriyah; M. Iqbal Tawakkal (International Journal of Education and Learning, 2025)
This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model in improving the argumentative essay writing skills of senior high school (SMA) students. Argumentative essay writing is a critical competency in Indonesian language learning, involving the ability to think critically, construct logical arguments, and systematically communicate ideas. The research method used was a quasi-experimental design with a pretest-posttest control group. The research subjects consisted of two 11th-grade classes in a public high school, assigned as the experimental and control groups. The instrument used was an argumentative essay assessment rubric including indicators of structure, cohesion-coherence, argumentation, and language use. The results showed a significant difference in the average essay writing scores between the experimental and control groups after the treatment. The PjBL model proved effective in enhancing students’ argumentative writing skills through active involvement, collaborative work, and the completion of real-world project-based tasks. These findings recommend the implementation of the PjBL model in writing instruction as an innovative alternative relevant to 21st-century learning needs.